2016
DOI: 10.4102/phcfm.v8i1.1230
|View full text |Cite
|
Sign up to set email alerts
|

Weight status and associated factors among HIV infected people on antiretroviral therapy in rural Dikgale, Limpopo, South Africa

Abstract: BackgroundUnderweight in human immunodeficiency virus (HIV)-infected people on antiretroviral therapy (ART) complicates the management of HIV infection and contributes to mortality, whereas overweight increases the risk of cardiovascular disease (CVD).AimThe study determined weight status and associated factors in people with HIV infection receiving ART.SettingRural primary health care clinics in Dikgale, Limpopo province, South Africa.MethodsA cross-sectional study in which data were collected using the World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(49 reference statements)
5
7
1
1
Order By: Relevance
“…This study demonstrates that those patients who had no regular mild to moderate physical activity are 1.3 times more likely to develop obesity/overweight compared to those participants with mild to moderate physical. This is in line with previous study in south Africa and Rwanda which showed People on ART who were not physically active were more likely to be overweight than those physically active (22,23). Physical activity may reduce the risk of being overweight and has a potential anti-inflammatory effect in people on ART.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates that those patients who had no regular mild to moderate physical activity are 1.3 times more likely to develop obesity/overweight compared to those participants with mild to moderate physical. This is in line with previous study in south Africa and Rwanda which showed People on ART who were not physically active were more likely to be overweight than those physically active (22,23). Physical activity may reduce the risk of being overweight and has a potential anti-inflammatory effect in people on ART.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous study in south Africa and Rwanda which showed People on ART who were not physically active were more likely to be overweight than those physically active. 21,22 Physical activity may reduce the risk of being overweight and has a potential anti-inflammatory effect in people on ART. On the other hand more physical activity increases the number of calories your body uses for energy or "burns off."…”
Section: Discussionmentioning
confidence: 99%
“…ART suppresses viral replication and increases CD4 count resulting in the restoration of recipients' health status [25]. us, the BMI change observed among the recipients herein might result from a natural process or interplay of different factors [11,15,26]. By preventing the advancement of HIV infection, ART allows other bodily processes to proceed normally and increase the recipients' weight.…”
Section: Characteristicsmentioning
confidence: 99%
“…e real contribution of ART on BMI change is therefore challenged and needs to be well defined. So far, only the restoration of recipients' health status through viral load suppression and CD4 cell increase attributed to ART is an indisputable fact [13][14][15]. e weight gain following sustained viral load suppression may be explained by multiple factors of which ART might not be a significant direct contributor.…”
Section: Introductionmentioning
confidence: 99%